Safety and efficacy of cryopreserved platelets in bleeding patients with thrombocytopenia. Issue 9 (11th September 2018) - Slichter, Sherrill J.; Dumont, Larry J.; Cancelas, Jose A.; Jones, MeLinh; Gernsheimer, Terry B.; Szczepiorkowski, Zbigniew M.; Dunbar, Nancy M.; Prakash, Gautham; Medlin, Stephen; Rugg, Neeta; Kinne, Bridget; Macdonald, Victor W.; et al.
Abstract : BACKGROUND: The short dating period of room temperature–stored platelets (PLTs; 5‐7 days) limits their availability at far‐forward combat facilities and at remote civilian sites in the United States. PLT cryopreservation in 6% DMSO and storage for up to 2 years may improve timely availability for bleeding patients. STUDY DESIGN AND METHODS: A dose escalation trial of DMSO‐cryopreserved PLTs (CPPs) compared to standard liquid‐stored PLTs (LSPs) was performed in bleeding patients with thrombocytopenia. Within each of four cohorts, six patients received escalating doses of CPP (0.5 unit, 1 unit, and sequential transfusions of 2 and 3 units) and one received a LSP transfusion. Patients were monitored for adverse events (AEs), coagulation markers, PLT responses, and hemostatic efficacy. RESULTS: Patients with a World Health Organization bleeding score of 2 or more received from 0.5 to 3 units of CPP (n = 24) or 1 unit of LSP (n = 4). There were no related thrombotic or other serious AEs experienced. Mild transfusion‐related AEs of chills and fever (n = 1), transient increased respiratory rate (n = 1), DMSO‐related skin odor (n = 2), and headache (n = 1) were observed after CPP transfusion. Among CPP recipients 14 of 24 (58%) had improved bleeding scores, including three of seven (43%) patients who had intracerebral bleeding. CPP posttransfusion PLT increments were significantly less than those of LSPs; however, days to next transfusion were the same. After transfusion, the CPP recipients had improvements in some variables of thrombin generation tests and thromboelastography. CONCLUSION: Cryopreserved PLT transfusions appear to be safe and effective when given to bleeding patients with thrombocytopenia.